Comparative Study of Neuroleadership and Managerial Demographics in Makati City Bank: Insights for Leadership Development - Jaazaniah S. Pavilion; Isabel D. Besana; Michael M. Caballero (People and Behavior Analysis, 2026)
This study investigates how managerial employees’ demographic profiles influence neuroleadership competencies in a Makati City bank. Neuroleadership encompasses four domains—decision-making & problem-solving, emotional regulation, collaboration & influencing others, and facilitating change —each critical in high-stakes financial environments. Using a quantitative, cross-sectional survey design, data were collected from 100 supervisors and managers aged 20 to 59 years. Non-parametric tests (Kruskal–Wallis and chi-square) were applied to assess differences and associations across demographic groups, including age, gender, length of service, industry experience, and leadership training. Results revealed consistently competent to high proficiency across all domains, suggesting strong cognitive and interpersonal leadership capabilities among respondents. Most demographic variables did not significantly affect neuroleadership outcomes, suggesting that competencies may develop uniformly across employees and are shaped more by organizational culture and standardized training than by demographic characteristics. Notable differences emerged only in tenure and leadership training, with longer service and recent training associated with stronger skills in facilitating change and influencing others. The study contributes empirical evidence from the underexplored Philippine banking sector and highlights practical implications for leadership development. Recommendations include scenario-based decision-making exercises, implementation-focused problem-solving workshops, and neuroscience-informed programs tailored for early-tenure employees.